Physical, chemical, and microbial contaminants in food waste management for soil application: A review. (1st May 2022) - O'Connor, James; Mickan, Bede S.; Siddique, Kadambot H.M.; Rinklebe, Jörg; Kirkham, M.B.; Bolan, Nanthi S.
Abstract: Currently, 1.3 billion tonnes of food are thrown away each year, most of which are incinerated or landfilled causing large environmental, social, and economic issues. Therefore, the utilisation of food waste as biofertilisers, such as composts and digestates, is a solution to reduce the problems created by incineration and landfilling whilst simultaneously amending soils. The improper disposal of food wastes and bulking materials can contribute to high levels of contaminants within the end-product. Moreover, the food waste and bulking materials, themselves, may contain trace amounts of contaminants. These contaminants tend to have long half-lives, are easily mobile within soil and plants, can accumulate within the food supply chain, and have moderate to high levels of toxicity. This review aims to examine the current and emerging contaminants of high concern that impact the quality of food-waste fertilisers. The paper presents the volume of current and emerging contaminants of plastics, other physical (particulate) contaminants, heavy metals, pesticides, polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), per- and polyfluoroalkyl substances (PFAS), and pathogens within food-waste composts and digestates. Due to the large extent of organic chemical contaminants and the unknown level of toxicity and persistence, the risk assessment of organic chemical contaminants in the food-supply chain remains largely unknown. This study has presented available data from literature of various contaminants found in food waste, and composts and digestates derived from food waste, and evaluated the data with current regulations globally. Overall, to reduce contaminants in composts and digestates, more studies are required on the implementation of proper disposal separation, effective composting and digestion practices, increased screening of physical contaminants, development of compostable plastics, and increased regulatory policies on emerging, problematic contaminants. Moreover, examination of emerging contaminants in food-waste composts and digestates is needed to ensure food security and reduce future human-health risks. Graphical abstract: Image 1 Highlights: Contaminants are found in food wastes and their subsequent composts and digestates. The review covers current and emerging contaminants of high concern. Many contaminants bioaccumulate and biomagnify within the food chain. A range of contaminants in food wastes, composts, and digestates is reviewed.